2016
DOI: 10.1021/acsami.6b08921
|View full text |Cite
|
Sign up to set email alerts
|

Counter Electrode Impact on Quantum Dot Solar Cell Efficiencies

Abstract: The counter electrode (CE), despite being as relevant as the photoanode in a quantum dot solar cell (QDSC), has hardly received the scientific attention it deserves. In this study, nine CEs (single-walled carbon nanotubes (SWCNTs), tungsten oxide (WO), poly(3,4-ethylenedioxythiophene) (PEDOT), copper sulfide (CuS), candle soot, functionalized multiwalled carbon nanotubes (F-MWCNTs), reduced tungsten oxide (WO), carbon fabric (C-Fabric), and C-Fabric/WO) were prepared by using low-cost components and facile pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…These two peaks resemble the first- and second-order diffraction peaks, suggesting the existence of crystal region. The first peak corresponds to a d-spacing of 3.6 Å, which is close to the typical π-π stacking distance, signifying that some PEDOT chains in SSP PEDOT have a well-ordered π-π stacking (Kumar et al., 2016, Sun et al., 2015b, Chen et al., 2017, Wang et al., 2018b, Rudd et al., 2018). However, the result cannot rule out the possibility that the crystalline PEDOT domains could be embedded in an amorphous PEDOT matrix (Rolland et al., 2018, Gueye et al., 2016).…”
Section: Resultsmentioning
confidence: 82%
“…These two peaks resemble the first- and second-order diffraction peaks, suggesting the existence of crystal region. The first peak corresponds to a d-spacing of 3.6 Å, which is close to the typical π-π stacking distance, signifying that some PEDOT chains in SSP PEDOT have a well-ordered π-π stacking (Kumar et al., 2016, Sun et al., 2015b, Chen et al., 2017, Wang et al., 2018b, Rudd et al., 2018). However, the result cannot rule out the possibility that the crystalline PEDOT domains could be embedded in an amorphous PEDOT matrix (Rolland et al., 2018, Gueye et al., 2016).…”
Section: Resultsmentioning
confidence: 82%
“…In a previous elaborate study by our group on CEs, we found that carbon (C)-fabric/WO 3−x serves as an excellent CE, for the cell with this CE exhibited the highest PCE of 4.6%, and this was attributed to the least polysulfide reduction potential, a reasonably good electrocatalytic activity, and a low sheet resistance of the C-fabric (9−15 Ω cm −2 ) and its meshlike morphology that maximized WO 3−x loading. 24 Here, QDSCs with the configuration TiO 2 −CBN/CdS/Au@PAA-polysulfide/SiO 2 gel−C-fabric/WO 3−x showed high PCEs, high fill factors (FFs), and reasonably good stabilities as well. The effect of carbonate treatment on stability and performance is explained, and how this treatment is effective in preserving high PCEs to some extent upon scale-up to large area cells with active areas of 1 cm 2 and even 4 cm 2 is also demonstrated.…”
Section: ■ Introductionmentioning
confidence: 84%
“…These two peaks resemble the first-and second-order diffraction peaks, suggesting the existence of crystal region. The first peak corresponds to a d-spacing of 3.6 Å , which is close to the typical p-p stacking distance, signifying that some PEDOT chains in SSP PEDOT have a wellordered p-p stacking (Kumar et al, 2016;Sun et al, 2015b;Chen et al, 2017;Wang et al, 2018b;Rudd et al, 2018). However, the result cannot rule out the possibility that the crystalline PEDOT domains could be embedded in an amorphous PEDOT matrix (Rolland et al, 2018;Gueye et al, 2016).…”
Section: The Molecular Packing Of Ssp Pedotmentioning
confidence: 95%